Analyzing the Regional Digital Potential in Social Sphere - Muhacheva Anna (Вестник Кемеровского государственного университета. Серия: политические, социологические и экономические науки)
Regional potential in the digital sphere is a promising research topic. The current approaches to digitalization assessment are limited to such objective and quantitative indicators as the quality of life, which fail toconsider public opinion. The article describes the methodological foundations for digital development in the social life across Russia as a categorical and structural model. After defining the digital potential of a region in the social sphere, the author analyzed the existing methods of its assessment and identified the directions of digital development as part of the regional management system. A set of standard methods combined with economic and statistical analysis made it possible to differentiate the concept in question from digital development, digital maturity, innovation potential, information potential, digitalization, digital transformation, etc. The concept of regional socio-digital potential was defined as a concise designation of the regional digital potential in the social sphere. Its structural and system model is presented. Such a factor in the development of the socio-digital development as the socio-digital profile of the region, i.e., a set of typological features of a particular territory.